Gambaran Perilaku Hidup Bersih dan Sehat (PHBS) pada Keluarga yang Mengalami Kekeringan di Desa Balerejo Kecamatan Panggungrejo Kabupaten Blitar - Adinda Putri Lestari (Journal of Ners and Midwifery, 2017)
Drought has impacts especially an impairment of health. To avoid from range of health problem expected to implement clean and healthy living when drought. The purpose of this research is to show clean and healthy living of families who have drought in the Village Balerejo in Panggungrejo Blitar District. This research design used descriptive design. Populations in this research is 620 families. This research used quota sampling technique with sample from 62 families in the Village Balerejo in Panggungrejo Blitar Distric. The data was collected by filling out of the questionnaires. The data was undertaken on February 27th to March 31st 2016. The result showed that clean and healthy living of families who have drought in strata 3 or less 59.7 % (37 families). From the thirteenth of indicators that have category less namely the using of clean water, using of privy health and eat fruits and vegetables every day. This influenced by a factor of age, education, environmental and cultural. Recommendations research is expected could give contributions in clean water supply and improvement and execution of the clean and healthy living in of families that experienced the drought.